THE NATURE AND THE AMOUNT OF WEAR OF PRESS-FIT CONNECTION OF AXLE UNIT CARS - Mykhalichenko, P. Ye. (Science and Transport Progress, 2005)
The article deals with results of statistical research of the wear quantity of inside surface of races and wheelset neck of the car. The parametrical reliability of the stationary joint has been defined with account of oval and conelike shape of the details.